Mass spectrometry insights into a tandem ubiquitin-binding domain hybrid engineered for the selective recognition of unanchored polyubiquitin - Scott, Daniel; Garner, Tom P.; Long, Jed; Strachan, Jo; Mistry, Sharad C.; Bottrill, Andrew R.; Tooth, David J.; Searle, Mark S.; Oldham, Neil J.; Layfield, Rob (Wiley-VCH Verlag, 2016)
Unanchored polyubiquitin chains are emerging as importanregulators of cellular physiology with diverse roles paralleling those of substrate-conjugated polyubiquitin. However tools able to discriminate unanchored polyubiquitin chains of different isopeptide linkages have not been described. We describe the design of a linker-optimised ubiquitin-binding domain hybrid (t-UBD) containing two UBDs, a ZnF-UBP domain in tandem with a linkage-selective UBA domain, which exploits avidity effects to afford selective recognition of unanchored Lys48-linked polyubiquitin chains. Utilising native MS to quantitatively probe binding affinities we confirm cooperative binding of the UBDs within the synthetic protein, and desired binding specificity for Lys48-linked ubiquitin dimers. Furthermore MS/MS analyses indicate that the t-UBD, when applied as an affinity enrichment reagent, can be used to favour the purification of endogenous unanchored Lys48-linked polyubiquitin chains from mammalian cell extracts. Our study indicates that strategies for the rational design and engineering of polyubiquitin chain-selective binding in non-biological polymers are possible, paving the way for the generation of reagents to probe unanchored polyubiquitin chains of different linkages and more broadly the ‘ubiquitome’.